Perbandingan Dual Banking System Indonesia dan Malaysia - Billa, Salsa; Soleha, Siti; Devitasari, Mimin (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2024)
A dual banking system is a financial practice that combines both interest and non-interest concepts in its operations. There are several countries that use dual banking systems in the Southeast Asian region, namely Indonesia and Malaysia. Therefore, the author wants to compare the dual banking system of Indonesia and Malaysia. Not all countries in the world use this dual banking system, therefore according to the author it is an interesting thing and will add to the knowledge of the readers. In writing this journal, the author applies a normative legal writing approach using a legal research method that focuses on secondary data analysis. The legal materials used are primary and secondary legal materials and use qualitative analysis techniques. Although both countries use a dual banking system, after making a comparison, there are 4 differences, namely regarding the history of the formation of the dual banking system, Islamic banking regulations, the structure of Islamic banking strategy development, and the contracts used in Islamic banking. The similarities can be seen in the Islamic banking institutional system and Islamic bank supervisory institutions.  It can be concluded that countries with dual banking systems have different developments and regulations to implement this system.